Iron overload and impaired iron handling contribute to the dystrophic pathology in models of Duchenne muscular dystrophy. Issue 3 (6th March 2022) - Alves, Francesca M.; Kysenius, Kai; Caldow, Marissa K.; Hardee, Justin P.; Chung, Jin D.; Trieu, Jennifer; Hare, Dominic J.; Crouch, Peter J.; Ayton, Scott; Bush, Ashley I.; Lynch, Gordon S.; Koopman, René
Abstract: Background: Oxidative stress is implicated in the pathophysiology of Duchenne muscular dystrophy (DMD, caused by mutations in the dystrophin gene), which is the most common and severe of the muscular dystrophies. To our knowledge, the distribution of iron, an important modulator of oxidative stress, has not been assessed in DMD. We tested the hypotheses that iron accumulation occurs in mouse models of DMD and that modulation of iron through the diet or chelation could modify disease severity. Methods: We assessed iron distribution and total elemental iron using LA‐ICP‐MS on skeletal muscle cross‐sections of 8‐week‐old Bl10 control mice and dystrophic mdx mice (with moderate dystrophy) and dystrophin/utrophin‐null mice ( dko, with severe dystrophy). In addition, mdx mice (4 weeks) were treated with either an iron chelator (deferiprone 150 mg/kg/day) or iron‐enriched feed (containing 1% added iron as carbonyl iron). Immunoblotting was used to determine the abundance of iron‐ and mitochondria‐related proteins. (Immuno)histochemical and mRNA assessments of fibrosis and inflammation were also performed. Results: We observed a significant increase in total elemental iron in hindlimb muscles of dko mice (+50%, P  < 0.05) and in the diaphragm of mdx mice (+80%, P  < 0.05), with both tissues exhibiting severe pathology. Iron dyshomeostasis was further evidenced by an increase in the storage protein ferritin ( dko : +39%, P  < 0.05) and ferroportin compared with Bl10 control mice ( mdx : +152% and dko : +175%, P  < 0.05). Despite having features of iron overload, dystrophic muscles had lower protein expression of ALAS‐1, the rate‐limiting enzyme for haem synthesis ( dko −44%, P  < 0.05), and the haem‐containing protein myoglobin ( dko −54%, P  < 0.05). Deferiprone treatment tended to decrease muscle iron levels in mdx mice (−30%, P  < 0.1), which was associated with lower oxidative stress and fibrosis, but suppressed haem‐containing proteins and mitochondrial content. Increasing iron via dietary intervention elevated total muscle iron (+25%, P  < 0.05) but did not aggravate the pathology. Conclusions: Muscles from dystrophic mice have increased iron levels and dysregulated iron‐related proteins that are associated with dystrophic pathology. Muscle iron levels were manipulated by iron chelation and iron enriched feed. Iron chelation reduced fibrosis and reactive oxygen species (ROS) but also suppressed haem‐containing proteins and mitochondrial activity. Conversely, iron supplementation increased ferritin and haem‐containing proteins but did not alter ROS, fibrosis, or mitochondrial activity. Further studies are required to investigate the contribution of impaired ferritin breakdown in the dysregulation of iron homeostasis in DMD.